Investigating the effect of powder manufacturing and reconstitution on casein micelles using asymmetric flow field-flow fractionation (AF4) and transmission electron microscopy. (January 2021) - Lie-Piang, Anouk; Leeman, Mats; Castro, Alejandra; Börjesson, Erik; Nilsson, Lars
Graphical abstract: Highlights: AF4 is a powerful method to study the size and properties of milk proteins. Proteins, aggregated proteins and casein micelles were individually detected. Casein micelles associate in 600–800 nm clusters during processing of milk powder. At reconstitution the casein micelles clusters disassociate in the first 20 min. The AF4 can be used as a validation for indirect characterisation of milk proteins. Abstract: Milk powders are commonly used for a variety of food products in which among others the milk proteins add to the properties of the products. Processing of milk can, depending on the processing parameters, change the size and structure of the proteins. These changes can be difficult to measure due to the polydispersity of milk components, which makes it a challenge to obtain direct information about the individual proteins. In this paper, the results from an investigation of casein micelle size, size distribution, and structure in reconstituted skim milk and the comparison with raw and pasteurized skim milk are reported. The investigation used asymmetrical flow field-flow fractionation (AF4) in combination with online UV, multi-angle light scattering (MALS), and refractive index (RI) detection and the results were confirmed by transmission electron microscopy (TEM). The results show that there is a difference in casein micelle size distribution between the differently processed milk samples. The casein micelles of the reconstituted milk were found to have a z-average radius of gyration of 72 nm and the casein micelles in the raw and pasteurized skim milk were 58 and 62 nm respectively. The AF4 and TEM data suggest that the cause of the larger casein micelle size is a layer of aggregated whey proteins associated with the casein micelles surface. Moreover, the TEM investigation showed that a larger proportion of the casein micelles are aggregated in reconstituted milk compared to raw and fresh skim milk. Investigation of the effect of reconstitution time shows that the amount of aggregated casein micelles decreases during the first 20 min of reconstitution. The results show that the AF4-method can provide detailed insights into the reconstitution process and properties of different milk samples. Hence, it can be used as a reference or validation for more indirect methods to track the reconstitution of milk powders.